Bioactivities and molecular networking-based elucidation of metabolites of potent actinobacterial strains isolated from the Unkeshwar geothermal springs in India - Mehetre, Gajanan T.; Vinodh, J. S.; Burkul, Bhushan B.; Desai, D.; Santhakumari, B.; Dharne, Mahesh S.; Dastager, Syed G (RSC Advances, 2019)
The bioactive potential of Actinobacteria endemic to hot springs has rarely been investigated. This study highlights the cultivable diversity and bioactivities of Actinobacteria associated with the Unkeshwar hot springs, India. Potent strains were evaluated for their biosynthetic potentials and metabolite analysis was performed using effective dereplication molecular networking tools. A total of 86 actinobacterial strains were isolated and grouped into 21 distinct genera, based on 16S rRNA gene sequence analysis. These strains included rare members such as Micromonospora, Marmoricola, Actinomadura, Cellulomonas, Cellulosimicrobium, Janibacter, Rothia, Barrentisimonas, Dietzia and Glycomyces. In antimicrobial screening, Micromonospora sp. strain GH99 and Streptomyces sp. strain GH176 were found to be potent antimicrobial strains. The metabolic extracts of these strains exhibited strong antimicrobial activity against Staphylococcus epidermidis (NCIM 2493), Shigella flexneri (NCIM 5265), Klebsiella pneumonia (NCIM 2098), and Salmonella abony (NCIM 2257). The extracts also displayed strong anti-biofilm and anticancer activities against Pseudomonas aeruginosa (NCIM 5029), Acinetobacter junii (NCIM 5188) and breast cancer cell line MCF7, respectively. Both strains also tested positive for the presence of the PKS biosynthetic gene cluster in their genomes. To effectively delineate the secondary metabolites, the extracts were subjected to MS/MS-guided molecular networking analysis. Structurally diverse compounds including the polyketides 22-dehydroxymethyl-kijanolide (GH99 strain) and Abyssomicin I (GH176 strain) were detected in the extracts. Interestingly, Brevianamide F was detected in the extract of Micromonospora, which has previously been mostly found in fungal species. Other compounds such as cyclic tripeptides, Cyclo(l-Pro-d-Ile) and Cyclo(d-Pro-l-Phe), were also identified in this strain. In summary, for the first time, we explored the diversity of Actinobacteria and evaluated their bioactive potential from the Unkeshwar hot springs. The potent strains isolated in the study could be useful in drug discovery programs.

Biodegradation of mixed polycyclic aromatic hydrocarbons by pure and mixed cultures of biosurfactant producing thermophilic and thermo-tolerant bacteria - Mehetre, Gajanan T.; Dastager, Syed G.; Dharne, Mahesh S. (Science of the Total Environment, 2019)
Applicability of thermophilic and thereto-tolerant microorganisms for biodegradation of polycyclic aromatic hydrocarbons (PAHs) with low water solubility is an interesting strategy for improving the biodegradation efficiency. In this study, we evaluated utility of thermophilic and thermo-tolerant bacteria isolated from Unkeshwar hot spring (India) for biodegradation of four different PAHs. Water samples were enriched in mineral salt medium (MSM) containing a mixture of four PAHs compounds (anthracene: ANT, fluorene: FLU, phenanthrenc: PHE and pyrene: PYR) at 37 degrees C and 50 degrees C. After growth based screening, four potent strains obtained which were identified as Aeribacillus pallidus (UCPS2), Bacillus axarquiensis (UCPD1), Bacillus siamensis (GHP76) and Bacillus subtilis subsp. inaquosorum (U277) based on the 16S rRNA gene sequence analysis. Degradation of mixed PAH compounds was evaluated by pure as well as mixed cultures under shake flask conditions using MSM supplemented with 200 mg/L concentration of PAHs (50 mg/L of each compound) for 15 days at 37 degrees C and 50 degrees C. A relatively higher degradation of ANT (92% - 96%), FLU (83% - 86%), PHE (16% - 54%) and PYR (51% - 71%) was achieved at 50 degrees C by Aeribacillus sp. (UCPS2) and mixed culture. Furthermore, crude oil was used as a substrate to study the degradation of same PAHs using these organisms which also revealed with similar results with the higher degradation at 50 degrees C. Interestingly, PAH-degrading strains were also positive for biosurfactant production. Biosurfactants were identified as the variants of surfactins (lipopeptide biosurfactants) based on analytical tools and phylogenetic analysis of the surfactin genes. Overall, this study has shown that hot spring microbes may have a potential for PAHs degradation and also biosurfactant production at a higher temperature, which could provide a novel perspective for removal of PAHs residues from oil contaminated sites. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Biodegradation; Biosurfactants; Crude oil; Mixed culture; PAHs; Thermophiles